PENGARUH LATIHAN RHEUMATIK TERHADAP PENURUNAN SAKIT GABUNGAN ANTARA LANJUTAN DI DESA SUDIMORO KECAMATAN TULANGAN KABUPATEN SIDOARJO - Lailil Fatkuriyah (Jurnal Kesehatan dr. Soebandi, 2014)
Aging process causes decreasing musculoskeletal function such as degeneration, erosion, and calcification of cartilage and joint capsule that manifest in decreasing joint movement width. Aging process also causes decreasing cellular immune function such as increasing inflammation activity in joint. The causes are contributed to joint pain among elderly. Nurse is expected to give a safe and healthy solution to reduce joint pain in elderly. This study was aimed to identify the effect of rheumatic exercise on decreasing joint pain among elderly. Design used in this study was quasy experimental. The population was elderly whose age were 65-70 years old in Desa Sudimoro Kecamatan Tulangan Kabupaten Sidoarjo in June-July 2010. Total sample were 18 respondents taken according to inclusion criteria. The dependent variable was joint pain which was measured by Burbonais pain scale. Data were then analyzed using Wilcoxon Sign Rank Test and Mann Whitney Test with level of significance is ≤0,05. Result showed that there was effect of rheumatic exercise on decreasing joint pain among elderly after intervention in intervention group (p=0,014 Wilcoxon Sign Rank Test). But, there was no difference between intervention group and control group after Rheumatic Exercise (p= 0,297 Mann Whitney Test). It could be concluded that there was no effect of rheumatic exercise on decreasing joint pain among elderly. Many factors contributed to this result such as respondent dietary pattern and activity pattern during the research which were beyond control of researcher. Further studies should more control respondent’s dietary pattern, activity pattern, quantity and quality of the rheumatic exercise by respondents to obtain more accurate results.